2019
DOI: 10.1177/2050640619861883
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic management of 345 small rectal neuroendocrine tumours: A national study from the French group of endocrine tumours (GTE)

Abstract: Introduction Small rectal neuroendocrine tumours are good candidates for endoscopic resection provided that complete pathological resection (R0) is obtained and their risk of metastatic progression is low. We conducted a large multicentre nationwide study to evaluate the outcomes of the management of non-metastatic rectal neuroendocrine tumours ≤2 cm diagnosed endoscopically. Patients and methods The medical records, the endoscopic and pathological findings of patients with non-metastatic rectal neuroendocrine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(73 citation statements)
references
References 34 publications
2
54
1
3
Order By: Relevance
“…median follow-up of 32 months; however, in two cases it led to patient death [10]. This study also revealed that the neuroendocrine origin of the polyps is suspected in a minority of cases on endoscopy, before the polypectomy is conducted, and even when the diagnosis is suspected, many of rNEN are removed with a snare polypectomy, justifying the continuous education of endoscopists in this field [10]. This conclusion is in accordance with the results of our study, which showed that endoscopists suspected polyps of neuroendocrine origin in only 37.5% of cases (9/24 lesions) [9].…”
Section: Reviewmentioning
confidence: 95%
See 3 more Smart Citations
“…median follow-up of 32 months; however, in two cases it led to patient death [10]. This study also revealed that the neuroendocrine origin of the polyps is suspected in a minority of cases on endoscopy, before the polypectomy is conducted, and even when the diagnosis is suspected, many of rNEN are removed with a snare polypectomy, justifying the continuous education of endoscopists in this field [10]. This conclusion is in accordance with the results of our study, which showed that endoscopists suspected polyps of neuroendocrine origin in only 37.5% of cases (9/24 lesions) [9].…”
Section: Reviewmentioning
confidence: 95%
“…This statement is based on the assumption that the diagnosis is made on endoscopy, and then the patient is referred for treatment, preceded by EUS. Unfortunately, this scenario is far from what occurs in real life, and in many cases, the neuroendocrine origin of the lesion is not suspected on endoscopy and the diagnosis is made retrospectively by a pathologist [10]. In the study by Fine C et al on a large group of 329 patients with small rNEN the suspicion of rNEN on endoscopy was made only in 18% of cases; despite REVIEW this, one third of those that were correctly recognised were removed by polypectomy [10].…”
Section: Management After Simple Polypectomy (What To Do When a Mistamentioning
confidence: 98%
See 2 more Smart Citations
“…When radical treatment is applied, the prognosis for rectal G1 NETs with the diameter up to 10 mm is very good, with nearly 100% 5-year survival rate, and these tumors do not even require followup [1]. Unfortunately, in spite of clear recommendations, what is apparent through our patient's story and other studies, is that majority of these lesions are resected with a snare polypectomy [2,3], what may lead to incomplete resection, and subsequently metastatic spread [2][3][4][5]. Moreover, the important factor that led to the fatal outcome was the fact that the patient was lost for follow-up.…”
mentioning
confidence: 99%